Assessment of pets (cats and dogs) in homes using electrostatic dust collectors and QPCR: new tools to evaluate exposure and risk of allergies. Issue 5 (1st November 2016) - Scherer, Emeline; Valot, Benoit; Vacheyrou, Mallory; Naegele, Alexandre; Knapp, Jenny; Rocchi, Steffi; Roussel, Sandrine; Millon, Laurence; Reboux, Gabriel
Abstract: Contradictory results are found in the literature concerning fungi, bacteria, and pet exposure and the risk of developing asthma. All these allergens have been thoroughly studied separately in cohort studies, and a variety of sampling and analytical methods are used. It is already possible to characterize fungi, mites, and bacteria by QPCR. The aim of our study is to evaluate QPCR systems to quantify the presence of cats and dogs in homes. Twenty-four houses were sampled with an Electrostatic Dust Collector which was analyzed by QPCR. Questionnaires on the presence of pets in homes were completed. The results from QPCR were correlated for real presence of cats and dogs, and highlighted indirect exposure. This study provides a useful screening tool that will be used in future large cohort studies, such as the ELFE cohort study.